EŞREF BİN MUHAMMED HAZA`İNU`S-SA`ADAT (İNCELEME-METİN-DİZİN) - İLHAN, NADİR (Fırat Üniveristesi, 1998)
Haza'inu's-Sa'adaât, which is our field of study is the only book about medicine written by Eşref bin Muhammed. The book was written with a language used by the common people in order to be understood easily. We tried to explain a transcriptioned text of the only known transcript of Hazainu's-Sa'adât. Haza'inu's-Sa'adaât which we studied was written by a doctor in Turkish to be understood easily in an area where Turks lived. Sixty six percent of the words of the book is Turkish. Although thirty four percent of the words had been derived from other languages, they are suitable for the syntax of Turkish language. Though vowel leright for the Turkish words of the transcriptioned text of Hazai'nu's-Sa'adât had not been shown, 37 words which are thought to have long vowel in word roats were determined and listed.Language harmony of the text can be said to be regularXjt can be said that there is a full harmony of the thickness and thinnes of trie- words in their roots and affixes. Although case affixes are usually mentioned in their real forms, they can be used instead of each other. But that kind of usage is not very common. In our text it was determined 26 affixes which make noun from noun, and 7 different affixes which make verb from nouns. There are 20 affixes which make noun from verb except gerundiums. Two affixes which make verb from verbs were used except voice affixes. Six affixes for causatives, two for both passive and reflective voice, one for reciprocal middle voice had been used. Negative form of the verbs are formed by using -mA suffix. Negative form of present tense is formed by using -mAz. Auxiliary verbs are used in making compound verbs. There are some examples dealing whit auxiliary verb of bil-. Stative verbs are formed by using the following auxiliary verbs; gör-, gel-, git-, kal-, tur-/dur- and it-. In our study, sentences were classified according to their structure, verbs and meaning. This study contains the sections of Introduction, Entrance, transcriptioned text, Grammatical Index-Dictionary, Frequency Index and Facsimile. 7 184
Keywords: Türk Dili ve Edebiyatı; Turkish Language and Literature